Prospective comparative study of quantitative X-ray (QXR) versus dual energy X-ray absorptiometry to determine the performance of QXR as a predictor of bone health for adult patients in secondary care - Amar Rangan; Lucksy Kottam; Stephen P Tuck; Paul D Scott; Maya Jafari; Terence Watson; Ben Lopez; Ben Crone; Tim Whitbread; Adam Ratcliffe (BMJ Open)
Objectives To evaluate a method of quantitative X-ray (QXR) for obtaining bone health information from standard radiographs aimed at identifying early signs of osteoporosis to enable improved referral and treatment. This QXR measurement is performed by postexposure analysis of standard radiographs, meaning bone health data can be acquired opportunistically, alongside routine imaging.Design The relationship between QXR and dual energy X-ray absorptiometry (DEXA) was demonstrated with a phantom study. A prospective clinical study was conducted to establish areal bone mineral density (aBMD) prediction model and a risk prediction model of a non-normal DEXA outcome. This was then extrapolated to a larger patient group with DEXA referral data.Setting Secondary care National Health Service Hospital.Participants 126 consenting adult patients from a DEXA clinic.Interventions All participants underwent a DEXA scan to determine BMD at the lumbar spine (L2–L4) and both hips. An additional Antero-Posterior pelvis X-ray on a Siemens Ysio, fixed digital radiograph system was performed for the study.Outcome Performance of QXR as a risk predictor for non-normal (osteoporotic) BMD.Results Interim clinical study data from 78 patients confirmed a receiver operator curve (area under the ROC curve) of 0.893 (95% CI 0.843 to 0.942) for a risk prediction model of non-normal DEXA outcome. Extrapolation of these results to a larger patient group of 11 029 patients indicated a positive predictive value of 0.98 (sensitivity of 0.8) for a population of patients referred to DEXA under current clinical referral criteria.Conclusions This study confirms that the novel QXR method provides accurate prediction of a DEXA outcome.Trial registration number ISRCTN98160454; Pre-results.